Quantum-Driven Sustainable Entrepreneurial Readiness: An Empirical Model of Intrinsic Motivation and Characteristics Technology (Proceeding International Collaborative Conference on Multidisciplinary Science, 2025)
The rapid advancement of Quantum Machine Learning (QML), emerging from the convergence of quantum computing and artificial intelligence, presents transformative opportunities for data-driven sustainable entrepreneurship. This study investigates the influence of QML on intrinsic motivation and how such motivation shapes Quantum-Driven Sustainable Entrepreneurial Readiness (QDSER) among digital-native entrepreneurs. Grounded in Self-Determination Theory (SDT), the research further examines the role of technology characteristics—specifically perceived usefulness and perceived novelty—as both direct and moderating factors within the proposed conceptual framework. Empirical data were collected through purposive sampling of undergraduate business students actively engaged in entrepreneurial practice. The data were analyzed using Structural Equation Modeling (SEM) with SmartPLS 3.0. The findings reveal that QML significantly enhances intrinsic motivation and positively contributes to QDSER. Intrinsic motivation exerts a strong influence on QDSER, while technology characteristics directly affect QDSER but do not significantly impact intrinsic motivation. This study introduces the novel construct of QDSER, representing entrepreneurial readiness shaped by quantum technological engagement and sustainability orientation. The integration of psychological and technological dimensions offers a fresh perspective on entrepreneurial preparedness in the quantum era. The findings contribute to the emerging literature on digital entrepreneurship by highlighting the motivational and technological pathways through which QML fosters sustainable entrepreneurial behavior. Practical implications include the need for entrepreneurship education to incorporate quantum-aware, motivation-driven approaches that align with the evolving technological landscape. This research opens avenues for further exploration into how QML can cultivate entrepreneurial mindsets and readiness among the digital generation, particularly in addressing global sustainability challenges through innovative, quantum-enabled solutions.